Development of Viva Video Digital Art as a Learning Media at SMA Negeri 8 Padangsidimpuan - Ariaji, Rizky; Suryani Harahap, Fatma; Arnita, Leli; Sah, Nasir; Husein Nasution, Ahmad; Fuady Dharma Harahap, Andes (KnE Social Sciences, 2023)
Video is an electronic media that is able to combine audio and visual technology together so as to produce a dynamic and interesting impression. The purpose of the study was to find out the assessment of expert validators in viva video learning media feasibility test based on BSNP questionnaire. The benefits of this research provide interesting and enjoyable learning activities so that students become more active in learning, as well as enrich the teacher’s knowledge about alternative learning media. The average result of all aspects of the standardized due diligence based on the BSNP questionnaire before revision 3.12 with validity criteria is quite good Quite valid and needs revision. Meanwhile, after revision 3.76 with validity criteria both {Valid and do not need revision (feasible)}. The development of viva video media in electrolyte and non electrolyte solution material is expected to be applied to students in school. Keywords: Viva Video; digital art; learning media; BSNP